2017
DOI: 10.14238/pi18.5-6.1978.123-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bacteriuria in Infants Suffering from Acute Gastroenteritis

Abstract: Urinary tract infection in infancy when

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…12,13 Conversely, there are a number of cohort and case control studies of children presenting with diarrhea that specifically studied the incidence of associated culture-proven UTIs. [14][15][16][17][18][19][20][21][22][23] In addition, 2 studies were discovered during our review of the literature that included reports of diarrhea in children diagnosed with UTIs. However, neither study specifically investigated for an association between UTIs and reports 13 The Ginsburg study seems to collaborate our findings in contrast to the study by Balat and Hill, 13 which showed only a 1% incidence of associated diarrhea of which viral infectious etiologies were documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Conversely, there are a number of cohort and case control studies of children presenting with diarrhea that specifically studied the incidence of associated culture-proven UTIs. [14][15][16][17][18][19][20][21][22][23] In addition, 2 studies were discovered during our review of the literature that included reports of diarrhea in children diagnosed with UTIs. However, neither study specifically investigated for an association between UTIs and reports 13 The Ginsburg study seems to collaborate our findings in contrast to the study by Balat and Hill, 13 which showed only a 1% incidence of associated diarrhea of which viral infectious etiologies were documented.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies looked at the spectrum of coinfections reported with UTIs, none investigated exclusively for diarrhea 12,13 . Conversely, there are a number of cohort and case control studies of children presenting with diarrhea that specifically studied the incidence of associated culture-proven UTIs 14–23 . In addition, 2 studies were discovered during our review of the literature that included reports of diarrhea in children diagnosed with UTIs.…”
Section: Discussionmentioning
confidence: 99%